The first complete mitochondrial genome of the critically endangered Malaysian giant turtle, Orlitia borneensis (Testudines: Geoemydidae) - Salleh, Mohd Hairul Mohd; Esa, Yuzine (Springer, 2024)
We present here the complete mitochondrial sequence of the critically endangered Malaysian giant turtle, Orlitia borneensis. The assembled mitochondrial genome includes 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, two ribosomal RNA genes (rRNAs), and one control region. This mitochondrial genome has been archived in the NCBI GenBank with accession number OQ808845. The Batagur control region is relatively smaller than O. borneensis and closer to Aldabrachelys gigantea, which suggests potentially that O. borneensis has undergone an expansion in the control region.